MiR-340 Is a Biomarker for Selecting Treatment Between Chemotherapy and Allogeneic Transplantation in Acute Myeloid Leukemia - Niu, Mingshan; Zhang, Ninghan; Wang, Rong; Shao, Tingting; Feng, Yuan; Shen, Yangling; Liu, Xuejiao; Zhao, Kai; Zhu, Shengyun; Xu, Linyan; Yao, Yao; Xu, Kailin (Frontiers in Oncology, 2019)
Acute myeloid leukemia (AML) needs refined risk stratification tools to drive decisions concerning optimal therapy strategies. In this study, we performed genome-wide screening to identify miRNA that could predict clinical outcome in a heterogeneous AML population using the TCGA dataset. We identified that miR-340 is a prognostic factor for selecting treatment between chemotherapy and allogeneic transplantation (allo-HSCT). In multivariable analyses, low miR-340 expression is predictive of reduced OS (HR=2.07, P=0.004) and EFS (HR=1.909, P=0.01) independent of other well-known prognostic factors. More importantly, allo-HSCT could overcome the adverse outcomes related to low miR-340 expression. The patients undergoing allo-HSCT had significantly better OS (HR=0.316, P<0.0001) and EFS (HR=0.391, P=0.002) compared with patients treated with chemotherapy in the low miR-340 expression group. In gene expression profiling, high miR-340 expression was negatively correlated with HOXA and HOXB cluster levels, as well as the amounts of the HOX cofactor MEIS1. Strikingly, HOXA10, HOXB2 and MEIS1 were in silico predicted targets of miR-340. The miR-340 expression may help identify cases requiring strategies for selecting the optimal therapeutic option between chemotherapeutic and allo-HCST regimens. AML cases with low miR-340 levels may be strongly considered for early allo-HSCT treatment.